Retraction Note to "Acid Induced Phytoconstituents of Calotropis procera Extract Combined with Ampicillin in Combating Clinical Resistant Isolates of Staphylococcus aureus and Salmonella spp." [Fine Chemical Engineering, Volume 5 Issue 1 (2024), 111-122] - Universal Wiser Publisher (Fine Chemical Engineering, 2025)
The Editor-in-Chief and the Editorial Office of Fine Chemical Engineering (FCE) have retracted the following article: Gideon, M.; Ladan, Z.; Yakubu, Y. Acid Induced Phytoconstituents of Calotropis procera Extract Combined with Ampicillin in Combating Clinical Resistant Isolates of Staphylococcus aureus and Salmonella spp. Fine Chemical Engineering 2024, 5, 111-122. Following a journal-wide investigation, it was identified that some cited references in this article are inappropriate to support the statements associated with them, or were used to support claims without referring to the primary sources that substantiate those claims. This indicates a lack of recognition and use of the broader relevant literature by the authors, which does not meet the journal’s academic and ethical standards. The retraction is in accordance with the Committee on Publication Ethics (COPE) guidelines, ensuring the integrity of the publication record is maintained. As part of the journal’s ongoing efforts to improve the quality of publications, the editorial office will continue to rigorously conduct preliminary review and peer review to ensure that only manuscripts that align with the journal’s scope and uphold the highest academic standards are published. The editorial office sincerely apologizes for any confusion or inconvenience this retraction may have caused.